A gestão de educação especial e a formação continuada da rede municipal de ensino de Marataízes/ES: a pesquisa-ação em foco - Silva, Nazareth Vidal da (2019)
The purpose of this work is to assess education professionals’ continuous formation and its connections with the modality special education under the school inclusion per spective. It seeks to understand special-education management, using critic collabo ration in the constitution of movements for continuous formation with/for professionals of the municipal public education system of Marataízes, ES, Brazil, under the school inclusion perspective. Theoretical contributions were the supposals of Communicative Action Theory, by German philosopher and sociologist Jürgen Habermas, using the epistemologic-methodologic perspective of critic-collaborative research-action, depart ing from critic-collaborative self-reflection principles. Participants were Municipal Edu cation Board staff, principals, pedagogues, ordinary-class teachers, special-education teachers, and university researchers. Study-reflection groups (the formation-assess ment group ‘Special Education Course under the Marataízes Inclusion Perspective’ and the ‘Marataízes Assessment and Research Group on Inclusive School Education’) were constituted as data-production’s main strategy; participant observation was also used, with field-diary registration, and audiotapes, later transcribed. Data were orga nized after content analysis. Analysis and interpretation are based on dialogue with theoretic-methodologic reference, besides other authors contributing for the discus sions around the themes crossing this work. Outcomes are linked to movements insti tuted for the continuous formation of education professionals, out of public managers’ actions, in partnership and collaboration with university. Thus, it is observed in the instituted formation movements that their participants see themselves as experiencing some maturation moment, belonging to and implicated in the transformation process, with perspective and concept changes about the way of doing continuous formation, and there is willingness to proceed.